Sobre a teoria da difração de raios-x em estruturas tridimensionais - Carlos Esteves Teixeira Junior (2014)
The ability to infer about the solid-state structure of matter by means of the radiation-matter interaction theory may be the most successful prospect in the crystallographic analysis. One of those perspectives regards the use of X-rays radiation to study crystalchemistry aspects of the analyzed material. The evaluation of X-rays diffraction data must be made following extensive strategies of information extraction. In this work, pure samples and their controlled mixes were the experimental materials to interpret and infer on, following an ab initio principle, the structure and composition of matter. Therefore, five samples were prepared, being composed of portions of pure quartz and hematite, following 1:0, 2:1, 1:1, 1:2 and 0:1 relative quantity ratios. All samples provided were scanned on a copper tube based diffractometer through the 3.01-79.99° range along the measured spectrum. The numerical results were subjected to evaluation by software meant to structural solution and refinement (CheckCell, FullProf and GSAs) and structural-compositional information was extracted (e.g., structure factor) considering the physical-mathematical framework of the phenomenon. All analyses carried out allowed inferring about the ability of minimization of squared errors based methods to determine or evaluate the crystal structure of minerals in multiphase mixtures. Additionally, the criticism on the quantitative phase analysis was done deductively allowing the comparison of different strategies for quantification (e.g., Rietveld-based methods, RIR) against a new procedure based on the modification of the phases structure factor. The intensity of diffraction peaks subject to anomalous effects was incorrectly interpreted by the classical methods, whilst the new approach developed in this work pointed out accurate results.